Cooperation and Trustworthiness in Repeated Interaction - Tobias Cagala; Ulrich Glogowsky; Veronika Grimm; Johannes Rincke (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Public goods provision often involves groups of contributors repeatedly interacting with administrators who can extract rents from the pool of contributions. We suggest a novel identification approach that exploits the sequential ordering of decisions in a panel vector autoregressive model to study social interactions in the laboratory. Despite rent extraction, contributors and administrators establish a stable interaction with cooperation matching the level from a comparable Public Goods Game. In the short run, temporary changes in behavior trigger substantial behavioral multiplier effects. We demonstrate that cooperation breeds trustworthiness and vice versa and that one-time disruptions are particularly damaging in settings with a lack of cooperative attitudes and trust.
Keywords: C32; C91; C92; H41; 330; Cooperation; trustworthiness; rent extraction; methods for laboratory experiments; panel vector autoregressive model